Development of time-variant landslide-prediction software considering three-dimensional subsurface unsaturated flow. (November 2016) - An, Hyunuk; Viet, Tran The; Lee, Giha; Kim, Yeonsu; Kim, Minseok; Noh, Seongjin; Noh, Jaekyoung
Abstract: An accurate landslide-susceptibility assessment is fundamental for preventing landslides and minimizing damage. In this study, a new time-variant slope-stability (TiVaSS) model for landslide prediction is developed. A three-dimensional (3D) subsurface flow model is coupled with the infinite slope-stability model to consider the effect of horizontal water movement in the subsurface. A 3D Richards' equation is solved numerically for the subsurface flow. To overcome the massive computational requirements of the 3D subsurface flow module, partially implicit temporal discretization and the simplification of first-order spatial discretization are proposed and applied in TiVaSS. A graphical user interface and two-dimensional data visualization are supported in TiVaSS. The model is applied to a 2011 Mt. Umyeon landslide in the Republic of Korea, and its overall performance is satisfactory. Highlights: A new time-variant slope-stability model for predicting rainfall-induced landslides is developed. The three-dimensional subsurface unsaturated flow and an infinite slope-stability model are combined. A graphical user interface including input and output visualization is supported.